Cooperating over losses and competing over gains: A social dilemma experiment - Alessandro Ispano; Peter Schwardmann (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
Evidence from studies in international relations, the politics of reform, collective action and price competition suggests that economic agents in social dilemma situations cooperate more to avoid losses than in the pursuit of gains. To test whether the prospect of losses can induce cooperation, we let experimental subjects play the traveler's dilemma in the gain and loss domain. Subjects cooperate substantially more over losses. Our experimental design allows us to show that this treatment effect is best explained by reference-dependent risk preferences and referencedependent strategic sophistication. We discuss policy implications and relate our findings to other experimental games played in the loss domain.
urn:nbn:de:bvb:19-epub-27576-4
Keywords: C90; D01; D03; D81; 330; cooperation; traveler's dilemma; social dilemma; loss domain; diminishing sensitivity; cognitive hierarchy